Kedudukan Pembeli Apartemen Sebagai Kreditor Dalam Hal Pengembang Dinyatakan Pailit: (Studi Perbandingan Hukum Antara Indonesia Dan India) - De Rosario, Veronica Ganesha; Tiurma Mangihut P.; Franzlay, Cristy (Yuriska: Jurnal Ilmiah Hukum, 2021)
Background: It is important for everyone to have a place to live, one of which is the concept of multi-storey housing which we usually know as flats or apartments. However, in the buying process, there are many injustices, especially when the developer is declared bankrupt. Indonesia is not firm and fair in its efforts to protect the rights of apartment buyers. In India, which provides more legal certainty and provides protection for the rights that should be obtained by the buyer. Research Metodes: The form of this research uses a normative juridical research form. The nature of this research is descriptive. The object of research that this author contains contains legal principles, where the object of research is sourced from secondary data and is supported by primary data. Qualitative research, namely data analysis with more emphasis on the quality or content of the data. In terms of drawing conclusions, the author uses a deductive mindset. Findings: By dismissal of judicial review appeal to make the apartment buyer’s position become a secured creditor in the developer’s bankruptcy case, apartment buyer’s debt in Indonesia is still classified as an ordinary debt which the repayment is applied for according to Articles 1131 KUH Perdata (civil code). Actually apartment buyers’ debt could be given a privilege rights position, but according to Articles 1134 of KUH Perdata (civil code), that rights must be granted in a statute. In India, the IBC receivables from apartment buyers are classified as a financial debt. Conclusion: Indonesia currently has the position of apartment consumers as concurrent creditors in bankruptcy, so it is different from India which has given apartment consumers the position as financial creditors based on section 5(8)(f) IBC 2018. So that the priority of paying apartment consumers’ receivables is aligned with bank receivables and other financial institutions.